ETNOBOTANI TUMBUHAN SUMBER PANGAN MASYARAKAT DAYAK BIDAYUH DI DESA HLI BUEI KECAMATAN SIDING KABUPATEN BENGKAYANG - Julia, Lusiana; Oramahi, H A; Hardiansyah, Gusti (Universitas Tanjungpura, 2020)
Food plants have long been used by local people of Hli Buei Village, Siding Subdistrict, Bengkayang District because of their simple processing and available in the forest. For generations, the village community has been accustomed to using food sources for their daily staple food needs. In addition, local food plants are still widely used because there is no market in Hli Buei Village. Until now, the use of plant food sources in Hli Buei Village, Siding Subdistrict, Bengkayang District has never been studied. Therefore, it is necessary to conduct research on the Ethnobotany of Plant Food for the Dayak Bidayuh Community in Hli Buei Village, Siding Subdistrict, Bengkayang District. The aim is to provide information about food plant species, utilization and processing of food source plants in Hli Buei Village, Siding Subdistrict, Bengkayang District. The research method is a survey method and data collection techniques by interview. Determination of respondents by purposive sampling in addition to observation and study of literature. Based on the results of interviews that have been conducted, there were 95 species from 44 families. The level of plant habitus that is widely used comes from the tree level (29.47%), herbs (28.42%), shrubs (22.1%), and the least is epiphyte (1.05%). The most part of the mash which used as food of the fruit, namely as many as 55 species (57.89%), leaves 17 species (17.89%) and the lowest was in the stems, shoots, tubers, flower buds, skin, fruit and heart, fruit. and umbut, fruit, tuber and water, terrace stem and tuber each 1 type (1.05%). Utilization of the most food plant groups came from the fruit group, namely 36 species (37.89%) and the lowest was the 3 species of cereals (3.15%).Keywords: Dayak Bidayuh, Ethnobotany, Plant FoodÂ